Combination Treatment of CI-994 With Etoposide Potentiates Anticancer Effects Through a Topoisomerase II-Dependent Mechanism in Atypical Teratoid/Rhabdoid Tumor (AT/RT) - Kim, Hee Yeon; Choi, Seung Ah; Koh, Eun Jung; Kim, Kyung Hyun; Phi, Ji Hoon; Lee, Ji Yeoun; Kim, Seung-Ki (Frontiers in Oncology, 2021)
Purpose Atypical teratoid/rhabdoid tumor (AT/RT) is arising typically in young children and is associated with a dismal prognosis which there is currently no curative chemotherapeutic regimen. Based on previous studies showing high histone deacetylase 1 (HDAC1) expression in AT/RT, the HDAC1 inhibitor CI-994 was used as a novel treatment strategy in this study. We assessed the anticancer effects of CI-994 and conventional drugs (etoposide, cisplatin or 4-HC) in AT/RT cells. Methods AT/RT patient-derived primary cultured cells and cell lines were prepared. HDAC1 was estimated by real-time quantitative polymerase chain reaction (RT-qPCR). The interaction of the drugs was analyzed using isobologram analysis. Cell viability, apoptosis, HDAC enzyme activity and western blot assays were carried out. Results HDAC1 was overexpressed in AT/RT compared to medulloblastoma. The combination index (CI) of CI-994 with etoposide revealed a synergistic effect in all AT/RT cells, but no synergistic effect was observed between CI-994 and cisplatin or 4-HC. CI-994 effectively reduced not only Class I HDAC gene expression but also HDAC enzyme activity. The combination treatment of CI-994 with etoposide significantly increased apoptosis compared to the single treatment. The enhanced effect of apoptosis by this combination treatment is related to a signaling pathway which decreases topoisomerase (Topo) II and increases histone H3 acetylation (Ac-H3). Conclusion We demonstrate that the combination treatment of CI-994 with etoposide exerts a synergistic anticancer effect against AT/RT by significantly inducing apoptosis through Topo II and Ac-H3 regulation. Clinical Relevance This combination treatment might be considered a viable therapeutic strategy for AT/RT patients.